2005
DOI: 10.1111/j.1365-3156.2004.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of an antigen detection dipstick assay for the diagnosis of human onchocerciasis

Abstract: SummaryTo improve on the diagnosis of onchocerciasis, especially light infections, we developed and evaluated an oncho-dipstick test based on the detection of Onchocerca volvulus specific antigens in urine and tears. The test was able to detect as little as 25 ng/ml of parasite specific antigens in samples and took as little as 3 h. Evaluation of the assay on 456 residents of an onchocerciasis hyperendermic area in Cameroon resulted in 408 (89.5%) positives in urine and 374 (82%) positives in tears. The preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…For example, a simple morbidity questionnaire administered through the existing education system allows the rapid delineation of high-risk areas of schistosomiasis haematobia, based on the specific symptomatology of Schistosoma haematobium, which is the presence of blood in urine (Lengeler et al, 2002). With regard to lymphatic filariasis, onchocerciasis and visceral leishmaniasis, accurate, non-invasive, rapid antigen detection assays applicable under field conditions have become available (Weil et al, 1997;Ayong et al, 2005;Chappuis et al, 2006). In the case of lymphatic filariasis, mapping of disease distributions has been based on the use immunochroDisease Causative agent(s) Rapid assessment approach Reference Schistosomiasis Schistosoma haematobium Morbidity questionnaires: reported blood in urine Lengeler et al, 2002 Schistosoma mansoni Morbidity questionnaires: reported blood in stool Lengeler et al, 2002 Close proximity to lakes (< 5 km) Lengeler et al, 2002 Lot quality assurance sampling Brooker et al, 2005 Schistosoma japonicum Morbidity questionnaires: reported blood in stool Zhou et al, 1998 Lymphatic matographic card tests (ICT) for the detection of circulating antigen from adult Wuchereria bancrofti filarial antigenaemia in order to target mass drug administration (Gyapong et al, 2002).…”
Section: The Proposalmentioning
confidence: 99%
“…For example, a simple morbidity questionnaire administered through the existing education system allows the rapid delineation of high-risk areas of schistosomiasis haematobia, based on the specific symptomatology of Schistosoma haematobium, which is the presence of blood in urine (Lengeler et al, 2002). With regard to lymphatic filariasis, onchocerciasis and visceral leishmaniasis, accurate, non-invasive, rapid antigen detection assays applicable under field conditions have become available (Weil et al, 1997;Ayong et al, 2005;Chappuis et al, 2006). In the case of lymphatic filariasis, mapping of disease distributions has been based on the use immunochroDisease Causative agent(s) Rapid assessment approach Reference Schistosomiasis Schistosoma haematobium Morbidity questionnaires: reported blood in urine Lengeler et al, 2002 Schistosoma mansoni Morbidity questionnaires: reported blood in stool Lengeler et al, 2002 Close proximity to lakes (< 5 km) Lengeler et al, 2002 Lot quality assurance sampling Brooker et al, 2005 Schistosoma japonicum Morbidity questionnaires: reported blood in stool Zhou et al, 1998 Lymphatic matographic card tests (ICT) for the detection of circulating antigen from adult Wuchereria bancrofti filarial antigenaemia in order to target mass drug administration (Gyapong et al, 2002).…”
Section: The Proposalmentioning
confidence: 99%
“…Antigen- or antibody-based diagnostic methods have been proposed but are not yet widely adopted [5]. However, even antigen or serological tests pose problems of suboptimal sensitivity or specificity [6][8]. Diagnosis of canine dirofilariosis relies on microscopic identification of circulating mf in the bloodstream, or adult antigen detection through a variety of commercially-available tests.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, skin snips are considered the "gold standard," but this method is becoming increasingly unpopular and is being replaced by PCR assays, ELISAs, enzyme immunoassays, and antigen surveys (6,7). A shortcoming of these newer assays is their inability to monitor disease progression readily.…”
mentioning
confidence: 99%